2010
DOI: 10.1590/s0100-204x2010000700017
|View full text |Cite
|
Sign up to set email alerts
|

Componentes não integrantes da carcaça de cabritos alimentados em pastejo na Caatinga

Abstract: Resumo -O objetivo deste trabalho foi avaliar o rendimento de buchada, os pesos e rendimentos de órgãos, vísceras e subprodutos da carcaça de cabritos, sem padrão racial definido, alimentados em pastejo na Caatinga, com ou sem suplementação. Dezoito cabritos machos castrados, com peso vivo inicial de 15±0,55 kg, foram mantidos em área de pastejo na Caatinga durante 105 dias. Os animais foram submetidos a três tratamentos em delineamento inteiramente ao acaso: pastejo à vontade, sem suplementação; pastejo restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
1
8
0
7
Order By: Relevance
“…The nutrient supply from the concentrate supplementation should not completely meet the requirements of animals, thus avoiding physiological energetic limitation by the chemostatic effect in the medial hypothalamus (satiety center), and the pasture should meet other needs (Ferdous et al, 2012). Setting the supplement at 1.5% BW is compatible with the research carried out with goats supplemented in the proportion of 1 to 1.5% BW with corn and soybean meal in pasture systems (Bezerra et al, 2010;Adami et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient supply from the concentrate supplementation should not completely meet the requirements of animals, thus avoiding physiological energetic limitation by the chemostatic effect in the medial hypothalamus (satiety center), and the pasture should meet other needs (Ferdous et al, 2012). Setting the supplement at 1.5% BW is compatible with the research carried out with goats supplemented in the proportion of 1 to 1.5% BW with corn and soybean meal in pasture systems (Bezerra et al, 2010;Adami et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The internal fat is highly variable and can be influenced by genotype (Rodrigues et al, 2013), nutrition (Bezerra et al, 2010), age, slaughter weight (Al-Owaimer et al, 2013), physiological condition, and physical activities (Solaiman et al, 2011). Higher visceral fat deposition can be explained by its more intense vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho Junior et al (2009), when evaluating carcass characteristics of crossbred (Boer × UB) goats subjected to three supplementation levels concluded that animals supplemented with up to 1% body weight had heavier carcass and commercial cuts. However, Bezerra et al (2010) observed that protein-energy supplementation to UB kids in the Caatinga during the dry season provided animals with higher body weight at slaughter and increased absolute weights of organs and viscera. Thus, the use of supplementation during the dry season is considered a good alternative to provide, in quantity and quality, nutrients that native pasture cannot supply and thus, increase the productivity of animals in order to meet market demands.…”
Section: Introductionmentioning
confidence: 95%